Two Way Stiffness Tuning Of Magnetorheological Elastomer- Shape Memory Alloy Composite. (2018) - Kumbhar, Samir B.; Chavan, S.P.; Gawade, S.S.
Abstract: Structural vibration control by tuning structural material modulus through external stimuli is great deal of interest for researchers. Shape memory alloy (SMA) is kind of smart material whose modulus can be varied by changing its temperature. Temperature dependent change in modulus of SMA during phase transformation is stiff and nonlinear which inducts difficulties for getting smooth structural stiffness change to alter its dynamic behavior. This paper deals with the work wherein, SMA is combined with magnetorheological elastomer (MRE) to form composite. MRE is another smart material whose shear modulus consequently stiffness can be changed by exposing it to variable magnetic field. Smart MRE-SMA composite has been studied analytically for stiffness variation by combining Maxwell form of three parameter constitutive viscoelastic material model, model for magnetic field dependent change in shear modulus for anisotropic MRE and temperature dependent modulus of SMA. The composite is fabricated, tested for stiffness change with respect to external stimuli by natural frequency measurement method and the results are compared with analytical study. The result show that the stiffness nonlinearity exists in SMA during transformation phase has been minimized by wisely selecting values of temperature and strength of magnetic field simultaneously. Significant level of smooth stiffness change is achieved by proper tuning of SMA temperature and strength of magnetic field.